A gradient-based adaptive balancing method for dedicated outdoor air system. (15th March 2019) - Cui, Can; Zhang, Xin; Cai, Wenjian; Jing, Gang
Abstract: This paper presents an online air balancing method applied in dedicated outdoor air systems, named as gradient-based online adaptive balancing (GOAB) method. The GOAB method derives the damper adjustment rule based on the gradient of the objective function that quantifies the discrepancy between actual flow rate and the set point in normalized form. An adaptive mechanism is applied to capture the change of Jacobian matrix during the balancing process. The optimum direction of damper angle increment is determined based on the null space of the gradient vector to speed up the convergence and ensure at least one damper to be fully open. Compared with the existing methods, the proposed GOAB method offers the following advantages:1.) The method can be performed on a duct system in operation, which provides possibility to re-balance the system under dynamic working conditions; 2.) The energy loss on dampers is minimized without compromising the balancing accuracy. Simulations are performed in MATLAB to investigate several model parameters and provide guidance for the parameter design. Experiments are conducted on a 5-ternimal duct system to validate the proposed method under various design flow requirements. The results show that the maximum absolute percentage error can be controlled within 4.3% among all test cases. This method improves the energy efficiency of the duct system and speeds up the convergence rate towards air balance to save time and cost. Highlights: An online air balancing method is proposed to balance the flow distribution in a duct system. A recurrent form of damper adjustment rule is proposed based on gradient descent. The optimum direction of the damper angle increment is found to minimize the energy loss. The proposed method requires little prior knowledge on the system topology and duct parameters. The proposed method is suitable for variational ventilation load applications.